2013
DOI: 10.1016/j.cemconres.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorated hardened cement paste structure analyzed by XPS and 29Si NMR techniques

Abstract: In this report, X-ray photoelectron spectroscopy (XPS) and 29 Si-MAS-NMR was used for the evaluation of deteriorated hardened cement pastes. The deterioration by ammonium 2 nitrate solution was accompanied by changes in the pore structure as well as by structural changes in the C-S-H in the hardened cement paste. The CaO/SiO2 ratio of the C-S-H decreased with the progress of deterioration, there was also polymerization of the silicate in the C-S-H. It was confirmed that the degree of polymerization of silicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…Figure illustrates the chemical shift in the reference and the white‐zone sample. As expected, in the reference sample only Q1 (chain end) and Q2 (within chain) peaks were visible, and neither Q3 or Q4 were observed, since chain structures were the major constituents in HCP . However, in the white zone, clear Q3 and Q4 peaks were observed, which indicated that branched and networked structures were formed due to a high degree of calcium depletion.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Figure illustrates the chemical shift in the reference and the white‐zone sample. As expected, in the reference sample only Q1 (chain end) and Q2 (within chain) peaks were visible, and neither Q3 or Q4 were observed, since chain structures were the major constituents in HCP . However, in the white zone, clear Q3 and Q4 peaks were observed, which indicated that branched and networked structures were formed due to a high degree of calcium depletion.…”
Section: Resultssupporting
confidence: 63%
“…It is well‐established that a 29 Si spectrum of the silicate anion is represented in the range of −70 to −76 ppm for Q0 (monomer), −78 for Q1 (dimer or end group in a chain), −81 to −85 for Q2 (chain), −93 to −102 for Q3 (branched structure), and −107 to −115 for Q4 (networked structure) . The average degree of C‐S‐H connectivity truetruen¯ is calculated as follows, n¯=Q1+2Q2+3Q3Q1+Q2+Q3. …”
Section: Methodsmentioning
confidence: 99%
“…This could be verified by the XPS analysis (Figure and Table S5). The increased binding energies of Si 2p in C0 and C3 as compared with C 3 S implied the higher degree in the polymerization of C–S–H gel after hydration of C 3 S . Considering that Ca 2+ could be coordinated with COO − replacing partial Na + and the structure of the guluronate blocks in SA allowed a high degree of coordination of Ca 2+ , the binding energy of COO − ···Ca 2+ bond was stronger than that of ironic COO − ···Na + bond, causing that the electron cloud density of O=C−O in COO − ···Ca 2+ tended to average as compared with that in COO − ···Na + .…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 3(b) displays the peak-fitted Ca 2p signals from PA0.0 (the red dotted line is the curve fitting results) [20]. All the Ca 2p spectra exhibited complex structures, with two main peaks centered at 346.9 eV and 350.3 eV, respectively.…”
Section: Xps Analysismentioning
confidence: 97%